Calories Value of Rice Husk Biobriquette Study as Potential of Renewable Energy in Indonesia - Suhirman, Suhirman; Toron, Yustinus S.; Sholehah, Inayatu (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Energy has an important role in supporting human life so that to get energy source we have to use natural resource optimally. Indonesia has been dependent on fossil fuels but its availability continues to experience scarcity. On the other hand Indonesia is a production country of rice and as the big consumer in the world. Unfortunately the rice husks are not used optimally. This review is knowing how to produce the rice husk briquettes and the factors that are affect quality of briquettes. This paper focus on the optimum factors include the type of adhesive, adhesive composition comparison, particle size, carbonization conditions, settler index and stability that are analyzed for knowing calories value of briquettes.